Chylothorax Associated with Congenital Complete Atrioventricular Block - Fujino, Shuhei; Maruyama, Hidehiko; Tsukamoto, Keiko; Ono, Hiroshi; Isayama, Tetsuya; Ito, Yushi (American Journal of Perinatology Reports, 2020)
Introduction Congenital complete atrioventricular block (CCAVB) associated with congenital chylothorax is a rare finding that has been reported in only one case in the literature. We report here the case of an infant with CCAVB complicated by congenital chylothorax.Patient Report We present the case of a male neonate with a birth weight of 2114 g. Fetal bradycardia and right pleural effusion were detected at gestational age of 22 weeks. Maternal serum levels of anti-Sjögren's-syndrome-related antigen A autoantibody were high (4840 U/mL). The neonate was delivered at gestational age of 33 weeks; a temporary external pacemaker was placed immediately after birth that resulted in an improved cardiac output. Milk-colored pleural effusion increased in volume together with the initiation of breast milk feeding. Lymphocytosis and high triglyceride levels in the pleural fluid led to the diagnosis of chylothorax. The pleural effusion resolved in response to prednisolone, octreotide, and total parenteral nutrition.Discussion The causal relationship between CCAVB and congenital chylothorax can be explained by considering the damage to the lymphatic vessels secondary to inflammation due to maternal autoantibodies and venous congestion due to bradycardia.Conclusion In any case of CCAVB associated with atypical pleural effusion, one must consider the possibility of congenital chylothorax.
Keywords: congenital complete atrioventricular block; congenital chylothorax; anti-SS-A/Ro antibody; prednisolone; octreotide; coagulation factor XIII